2020
DOI: 10.1590/1983-21252020v33n427rc
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF GIBBERELLIN ON GROWTH AND DEVELOPMENT OF Spondias tuberosa SEEDLINGS

Abstract: The development of technologies will certainly contribute to boost the commercial exploitation and domestication of Spondias tuberosa. The objective of the present study was to identify morphophysiological effects of gibberellin on the growth of S. tuberosa seedlings. The experiment was conducted in a greenhouse at the Goiás State University, Brazil, using 300-day-old S. tuberosa seedlings planted in 12-liter pots containing soil (Typic Hapludox), sand, and manure (3:1:0.5). The experiment was conducted in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The application of GA 3 promotes the expression of genes related to cell elongation, expansion, and division in tomato [4]. GA 3 application significantly promoted the elongation of the root, stem, and leaf cells of Spondias tuberosa plants [41]. Eriksson et al [42] indicated that elevated GA levels increase the number of internode cells in poplar (Populus) trees but do not affect the length of epidermal cells or pith cells.…”
Section: Discussionmentioning
confidence: 99%
“…The application of GA 3 promotes the expression of genes related to cell elongation, expansion, and division in tomato [4]. GA 3 application significantly promoted the elongation of the root, stem, and leaf cells of Spondias tuberosa plants [41]. Eriksson et al [42] indicated that elevated GA levels increase the number of internode cells in poplar (Populus) trees but do not affect the length of epidermal cells or pith cells.…”
Section: Discussionmentioning
confidence: 99%
“…PGR act influencing the synthesis, transport, or degradation of hormones, and for that reason, they may disturb other physiological processes that are controlled by those hormones. Examples of side effect are the reduced height growth of barley (Hordeum vulgare) sprayed with trinexapac-ethyl for delaying flowering time (Kupke et al, 2022), the reduction of specific leaf weight of Spondias tuberosa seedlings treated with gibberellin for improved rooting (Matos et al, 2020), the reduced sensibility to defoliants and delayed maturity of cotton plants sprayed with mepiquat chloride for chemical pruning (Qi et al, 2022), and the depressed seed yield of soybean treated with paclobutrazol for reducing lodging (Pricinotto & Zucareli, 2014).…”
Section: /8mentioning
confidence: 99%
“…Trinexapac-ethyl, paclobutrazol, mepiquat chloride, and chlormequat chloride are PGR that inhibit the synthesis of gibberellins and are used aiming to restrict the height growth of plants and several other characteristics, such as the leaf color for ornamental purpose (Teixeira et al, 2022), the rate of lodging (Souza et al, 2022), tillering (Ervin & Koski, 1998), time for flowering (Kupke et al, 2022), time for seed maturation (Qi et al, 2022), and seed yield (Ferrari et al, 2022). Gibberellin, with the opposite effect, is the main hormone for the promotion of stem elongation, and it is also used for promoting seed germination and flowering of many species (Castro-Camba et al, 2022), to improve yield and quality of mung bean (Vigna radiata) (Islam et al, 2021), and to promote rooting and initial growth of Spondias tuberosa seedlings (Matos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on their limitations and potentialities in the efficient use of water can promote better exploitation and expansion of this crop in regions with water deficit. Proper management of irrigation interval can favor water reserve in the soil to meet the water requirements of plants (SILVA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%